2023
DOI: 10.3389/fimmu.2023.1128151
|View full text |Cite
|
Sign up to set email alerts
|

Phosducin-like 3 is a novel prognostic and onco-immunological biomarker in glioma: A multi-omics analysis with experimental verification

Abstract: Malignant glioma is the most frequent primary tumor of the central nervous system. PDCL3 is a member of the phosducin-like protein family, and its imbalance has been shown to be associated with several human diseases. However, the underlying role of PDCL3 in human malignant cancers, especially in malignant gliomas, is unclear. In this study, we combined public database analysis and experimental verification to explore the differential expression, prognostic value and potential functions and mechanisms of PDCL3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Concerning methylation, however, DNASE1L3 was positively correlated the strongest with DNA stemness score in TGCT among all cancers [70]. Notably, in a different study, DNA stemness score was also positively correlated with the overexpression of a gene, namely PDLC3, and no correlation with overall survivor or progression-free survival was found [71]. In a study on the signal and transducer and activator of transcription (STAT) family, however, a negative correlation between DNA stemness score and STAT5A expression was found in TGCT, while this gene's overexpression was strongly associated with poor overall survival [72].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 84%
“…Concerning methylation, however, DNASE1L3 was positively correlated the strongest with DNA stemness score in TGCT among all cancers [70]. Notably, in a different study, DNA stemness score was also positively correlated with the overexpression of a gene, namely PDLC3, and no correlation with overall survivor or progression-free survival was found [71]. In a study on the signal and transducer and activator of transcription (STAT) family, however, a negative correlation between DNA stemness score and STAT5A expression was found in TGCT, while this gene's overexpression was strongly associated with poor overall survival [72].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 84%
“…Further survival analysis indicated that patients with high PDCL3 expression in tumors and low macrophage infiltration had a poorer prognosis, partly attributed to reduced macrophage infiltration. Previous research on immune infiltration in glioblastomas suggested that M2-type macrophage infiltration influences glioblastoma patient prognosis through angiogenesis regulation, extracellular matrix remodeling, and glioblastoma cell invasiveness [ 35 ]. Therefore, we hypothesize that high PDCL3 expression in LIHC affects the biological behavior of tumors by reducing macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PDCL3 is found to play an important role in apoptosis, possibly because PDCL3 adjuvants the folding of one or more pro-apoptotic factors 10 . Other studies have illustrated that differential expression or mutations in PDCL3 are associated with the development and progression of malignant gliomas 11 , fetal megacystis-microcolon 12 , and Alzheimer's disease 13 . Thus, PDCL3 is a key protein involved in tumor progression, however, its role in the pathogenesis of HCC has not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%